Multi-instant switching control of nonlinear networked systems under unreliable wireless digital channels. Issue 9 (June 2017) - Xie, Xiangpeng; Yue, Dong; Peng, Chen
Abstract: Integrating wireless networks in control systems allow users to take benefit from modular and flexible system design, but the analysis and design of such systems pose new challenges such as more serious packet loss. This study develops a new multi-instant switching controller of nonlinear networked systems under unreliable wireless digital channels. The proposed controller can be viewed as an improvement of previous results concerned with the homogenous polynomials approach, since it presents a denser subdivision of the joint space of multi-instant normalized membership functions and therefore essentially yields an efficient multi-instant switching mechanism for the first time. As a result, more efficient results can be obtained in the study. Finally, an illustrative example is provided to demonstrate the effectiveness of the multi-instant switching controller.